Liminality, Rock Art and the Sami Sacred Landscape - Mulk, Inga-Maria; Bayliss-Smith, Tim (Journal of Northern Studies, 2007)
The paper suggests that cultural landscapes were permeated by religious meanings in all pre-modern societies, including Sami societies before c. AD 1600. We suggest that knowledge of this sacred landscape was not restricted to an elite or to shamans, but was widely shared. For the Sami, religious rituals and associated images (e.g. rock art) involved all levels within a social hierarchy that linked the individual adult or child, the family, the band or sijdda, and the association of family groups or vuobme. We can decode the sacred landscapes of such societies if we can reconstruct sites of perceived anomaly and liminality in the landscape. This is discussed in the article with reference to Proto-Uralic cosmology in general and the Sami world-view in particular. The concepts of anomaly and liminality enable us to interpret the Badjelánnda rock art site in Laponia, northern Sweden, as not only a place of resource procurement (asbestos, soapstone) but also a sacred site. We suggest that the Badjelánnda site should be seen as a gateway to the Underworld, and therefore visits for quarrying, human burials at the site, or wild reindeer hunting in the vicinity were marked by ritual acts, directed perhaps towards the Sami female deity Máttaráhkká. The rock art should therefore be interpreted as an aspect of religious ritual, and in a context where anomalous topography signified that the Badjelánnda site was necessarily a liminal place.